Program Bangun Duniamu: Peningkatan Keterampilan Spasial Siswa Tunanetra Melalui Media Pembelajaran Denah - Prastika, Heni Duwi; Sadiya, Hasna Inas; Sholehah, Farida Lailatus; Rahmawati, Nur; Safitri, Shovia; Rofiki, Imam (JRCE (Journal of Research on Community Engagement), 2025)
Mobility is the main ability that must be mastered by a blind person, to be able to master it requires orientation skills that are built through mastery of spatial skills. Spatial skills are taught to blind students at SLB ABD Negeri Kedungkandang through Orientation and Mobility (O&M) activities. However, the school complained that O&M in the school environment could not be taught ideally because students had not mastered the basic stages and there was no supporting media. The Bangun Duniamu program is here to provide solutions to partners with the aim of (1) Improving spatial understanding through the use of floor plan learning media; and (2) Improving spatial skills to develop perception at the basic stages of Orientation and Mobility. The Bangun Duniamu program is implemented using the PDCA method, namely: (1) Plan; (2) Do; (3) Check; and (4) Act. Continued with the closing of the program and preparation of the report. The Bangun Duniamu program provides results in the form of an increase in spatial understanding from 4% to 64% through Deko Edu activities and an increase in spatial skills from 15% to 70% through Deko Action activities. These results have a positive impact on blind students, namely: (1) Spatial understanding in the form of good knowledge of routes, locations and distances; (2) Mastery of developing school environmental perspectives and independent mobility skills.